Following McWhinney's footsteps: from family medicine to traditional and complementary medicine - Armando Henrique Norman; Charles Dalcanale Tesser
Family physicians have developed a holistic approach to patients' care which can facilitate a mutual understanding of different Traditional and Complementary Medicine (T&CM) practices. This analytical paper considers three intertwined issues: (1) Ian McWhinney's critique of biomedical abstractions (i.e., disease categories); (2) The similarity between the cosmology of family medicine's organismic thinking and homeopathy's vitalism as an example of T&CM; and (3) The gradient of explanatory models (EMs) to delineate the space within which T&CM can be applied to patients' care. In primary health care predominates a blend of physiopathological and semiological EMs comprised of low to moderate risk patients. In this scenario, the introduction of T&CM practices can enhance family physicians' therapeutic scope. Thus, the combination of gradient of EMs, primary health care attributes, and family physicians' professionalism can provide the required safe environment for implementing T&CM services.